Everything You've Always Wanted to Know aboutAMJ(But May Have Been Afraid to Ask) - Rynes, Sara L.; Hillman, Amy; Ireland, R. Duane; Kirkman, Bradley; Law, Kenneth; Miller, C. Chet; Rajagopalan, Nandini; Shapiro, Debra (Academy of Management Journal, 2005)
This article presents information regarding the policies of the “Academy of Management Journal” for accepting and publishing submissions. The editors are looking for work that contributes to theory and has meaningful new insights. They strongly suggest peer reviews of research prior to data collection and recommend consulting “Publishing in the Organizational Sciences,” for more information. It also describes the publication's mission regarding the support of research into management theory and management practice.